Signs through Songs: A Semiotic Analysis of Self-Confidence Lyrics - Denisa Cevania; Diah Merrita (e-LinguaTera, 2023)
This study investigates denotative and connotative meanings in the lyrics of three songs using Barthes’ notion of semiotics. It is conducted in order to find out the meaning of self-confidence within them by unpacking the messages appeared. This study employs descriptive qualitative research. The result reveals that all three songs contain self-confidence meanings through the denotative and connotative meanings within the song lyrics in each stanza. The lyrics implied that listeners should be able to build their self-confidence in order to face the challenges ahead and support others so that they can live peacefully without having no conflict with others.